Pengaruh Media Powtoon dalam Mata Pelajaran Pendidikan Agama Islam terhadap Hasil Belajar Siswa Kelas VII - Sulaiman Sulaiman; Muthia Rahmayani (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The lack of media use and the subpar academic performance of seventh graders at SMP Negeri 2 Bukittinggi are the driving forces for this study. 1) The primary objective of this study is to identify the learning process using Powtoon as a medium. 2) to assess educational results utilizing Powtoon media 3) to assess the effect of Powtoon media on seventh-grade students' academic achievement at SMP Negeri 2 Bukittinggi. Experimental quantitative research is used in this work. Students from SMP Negeri 2 Bukittinggi's classes VII.1 and VII.2 made up the study's population. Purposive sampling was used as the sample method in this study. Tests of student learning outcomes, surveys, and documentation were used to gather data. The findings of the study were evaluated using the lndependent Sample T-Test. based on the research's conclusions from a survey 1) The average (Mean) usage of Powtoon media was 101.13, and 35% of students fell into the adequate category. 2) Up to 20% of pupils fall into the sufficient category for learning outcomes, as shown by an average score of 83.26. 3) The R square test result of 0.643 (64.3%) which demonstrates a relationship between the independent and dependent variables demonstrates that Powtoon media has an impact on class VII students at SMP Negeri 2 Bukittinggi's learning outcomes.